EDWF-MTTF-based heuristic scheduling algorithm in time-sensitive networks - Chuanhuang LI; Junhu LIAO; Jiadong XUAN; Qi XU; Huifeng ZHANG; Jun ZHU; Tao ZOU; Ruyun ZHANG (Dianxin kexue)
With the rapid integration and development of industrial control and information networks, time-sensitive networks based on ethernet have received widespread attention.In these networks, time-triggered communication scheduling is adopted to ensure the determinacy of data transmission.However, existing scheduling algorithms have struggled to rapidly calculate the scheduling tables for large-scale periodic traffic.Therefore, a heuristic scheduling algorithm based on the earliest deadline with weight first-maximum transfer time first was designed.This algorithm, by flexibly adapting traffic sorting weights and enhancing backtracking methods, could resolve the scheduling issues of large-scale traffic in industrial automation scenarios in a relatively short time.Experimental results show that compared to the classic integer linear programming method, the earliest deadline with weight first-maximum transfer time first heuristic scheduling algorithm is able to calculate a more optimal solution for the scheduling table of large-scale periodic traffic more swiftly.